Targeting the NLRP3 Inflammasome via BTK - Weber, Alexander N. R. (Frontiers in Cell and Developmental Biology, 2021)
The NLRP3 inflammasome represents a critical inflammatory machinery driving pathology in many acute (e.g. myocardial infarction or stroke) and chronic (Alzheimer's disease, atherosclerosis) human disorders linked to the activity of IL-1 cytokines. Although the therapeutic potential of NLRP3 is undisputed, currently no clinically approved therapies exist to target the NLRP3 inflammasome directly. The recent discovery of BTK as a direct and positive regulator of the NLRP3 inflammasome has, however, raised the intriguing possibility of targeting the NLRP3 inflammasome via existing or future BTK inhibitors. Here I review the mechanistic basis for this notion and discuss the molecular and cellular role of BTK in the inflammasome process. Specific attention will be given to cell-type dependent characteristics and differences that may be relevant for targeting approaches. Furthermore, I review recent clinical evidence for effects of BTK inhibitors on NLRP3 activity and highlight and discuss open questions and future research directions. Collectively, the concept of targeting BTK to target NLRP3-dependent inflammation will be explored comprehensively at the molecular, cellular and therapeutic levels.